2006
DOI: 10.4049/jimmunol.177.11.7715
|View full text |Cite
|
Sign up to set email alerts
|

B Cell-Mediated Antigen Presentation Is Required for the Pathogenesis of Acute Cardiac Allograft Rejection

Abstract: Acute allograft rejection requires the activation of alloreactive CD4 T cells. Despite the capacity of B cells to act as potent APCs capable of activating CD4 T cells in vivo, their role in the progression of acute allograft rejection was unclear. To determine the contribution of B cell APC function in alloimmunity, we engineered mice with a targeted deficiency of MHC class II-mediated Ag presentation confined to the B cell compartment. Cardiac allograft survival was markedly prolonged in these mice as compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
94
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(101 citation statements)
references
References 37 publications
5
94
0
1
Order By: Relevance
“…Recent studies by Naji and colleagues revealed that allograft rejection is impaired in recipients with MHC class II-deficient B cells, which are unable to engage in cognate interactions with CD4 ϩ T cells (30). These observations support the notion that B cells may be critical APCs for stimulating alloreactive CD4…”
supporting
confidence: 75%
“…Recent studies by Naji and colleagues revealed that allograft rejection is impaired in recipients with MHC class II-deficient B cells, which are unable to engage in cognate interactions with CD4 ϩ T cells (30). These observations support the notion that B cells may be critical APCs for stimulating alloreactive CD4…”
supporting
confidence: 75%
“…These are preferentially taken up by APCs via their Fc or complement receptors, eventually leading to their maturation and potent stimulation of alloreactive T cells (38,39). A study by Noorchashm et al (40) confirmed that B cells themselves can effectively act as APCs and are an important contributor to T cell activation and allograft rejection in a murine cardiac allograft model. This work was extended by Burns et al (41), who showed that preformed alloantibodies caused resistance to tolerance induction protocols.…”
Section: Discussionmentioning
confidence: 81%
“…A lthough B-cells have been primarily considered antibody-producing cells, recent studies demonstrate that they participate in the priming of autoimmune responses (1,2). Many investigations have examined the role of B-cells as antigen-presenting cells (APCs) in the generation of autoreactive T-cell responses (3,4).…”
mentioning
confidence: 99%